Ginkgetin exerts anti-inflammatory effects on cerebral ischemia/reperfusion-induced injury in a rat model via the TLR4/NF-κB signaling pathway. Issue 4 (3rd April 2019) - Li, Qin; Ye, Tao; Long, Ting; Peng, Xuemei
ABSTRACT: Ginkgo biloba, a natural biflavonoid isolated from Ginkgo biloba leaves, is reported to have strong anti-inflammatory and immunosuppressive properties. The aim of this study is to investigate the potential anti-inflammatory mechanisms of ginkgo flavonoids on cerebral ischemia/reperfusion (I/R) injury. Inflammatory-associated cytokines in cerebral ischemic hemispheres were determined by immunohistochemical staining, Western blot and enzyme-like immunosorbent assay (ELISA). Our results indicated that treatment with Ginkgetin significantly restored rat brain I/R-induced neurological deficit scores. Inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) expression in Ginkgetin treatment group (100 mg/kg) also significantly reduced. The expression inflammation-related protein prostaglandin E2 (PGE2), tumor necrosis factor alpha (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6) and interleukin-8 (IL-8) was also decreased in Ginkgetin treatment group. However, the expression of interleukin-10 (IL-10) was remarkably increased. Thus, this study demonstrates that Ginkgetin protects neurons from I/R-induced rat injury by down-regulating pro-inflammatory cytokines and blocking the TLR4/NF-κB pathway. Graphical abstract: : Ginkgetin protects neurons from I/R-induced rat injury by down-regulating pro-inflammatory cytokines and blocking the TLR4/NF-κB pathway.